Initial Experience With Patent Ductus Arteriosus Ligation in Pre-term Infants With Bidirectional Shunt Pattern - Yang, Ming-Chun; Liu, Hsien-Kuan; Wu, Hsuan-Yin; Tey, Shu-Leei; Yang, Yung-Ning; Wu, Chien-Yi; Wu, Jiunn-Ren (Frontiers in Pediatrics, 2020)
Background Patent ductus arteriosus (PDA) with a bidirectional shunt reflects critical clinical conditions. The operability of PDA with a bidirectional shunt in preterm infants is still not clearly clarified. This study aimed to investigate the feasibility and the outcomes of PDA ligation in preterm infants with a bidirectional shunt PDA. Methods All preterm infants receiving PDA ligation between 2013 and 2019 were enrolled in this prospective study. Patients were allocated into two groups based on the shunting direction of PDA, which were the left-to-right group (group A) and the bidirectional group (group B). Clinical characteristics and pre-op comorbidities were analyzed. Intraoperative complications, post-op neurological sequelae, necrotizing enterocolitis, survival, and mortality were compared between these two groups. Results Thirty-seven preterm infants were enrolled (18 in group A, 19 in group B). The mean postmenstrual age at PDA surgery was 32.0  1.3 and 32.8  1.5 weeks respectively. Before surgery, 44.4% and 89.5% (group A vs. B) of the patients were using invasive mechanical ventilator (p < 0.01). The requirement of high-frequency oscillatory ventilatory support was significantly higher in group B. PDA rupture-related bleeding during exposing PDA or ligating PDA occurred in four infants, and all were all in group B, including one with delayed hemothorax. Early surgical mortality within 30 days of surgery was higher in group B (0% vs. 21.1%, p < 0.05), but only one death could be attributed to the surgery, which was caused by a pain-induced pulmonary hypertension crisis. The 5-year survival was 100% in group A, and 73.7% in group B (p < 0.05). Conclusion We did not recommend routine PDA ligation in preterm infants with a bidirectional shunt. However, a bidirectional shunt should not be an absolute contraindication if they fulfill indications of PDA closure. Unexpected intraoperative PDA rupture and delayed hemothorax in a bidirectional shunt PDA should be carefully monitored. Aggressive post-op pain control is also warranted to avoid pulmonary hypertension crisis. The post-op early mortality rate was higher in the bidirectional group, which could be inherent to their poor pre-operative lung condition. Only one death was directly related to the surgery.